Proteomics of an Orphan Legume, Grasspea: Current Status and Future Strategy - Rathi, Divya; Chakraborty, Subhra; Chakraborty, Niranjan (Plant Tissue Culture and Biotechnology, 2015)
Orphan legumes are defined as those which are grown as food, animal feed and/or other legumes of agriculture importance, but which have received very little research attention. Grasspea is one of the best examples of such legume which is cultivated worldwide, as it is the cheapest source of dietary protein particularly for the developing world. It has remained outside the realm of largescale functional genomics studies. Many grasspea cultivars are capable to withstand a myriad of constraints, not only the common abiotic stresses, but pests and pathogen attack making it one of the potential systems to study stress tolerance. In recent years, most of its traits that interest biologists worldwide, such as stress tolerance, have rated so high that a number of new initiatives have been taken by different research groups for better and safer use of grasspea. In this review, we discuss the progress made in the field of grasspea proteomics to date and dwell upon the future direction/problems/approaches towards defining the grasspea proteome. Plant Tissue Cult. & Biotech. 25(1): 117-141, 2015 (June)